Modelo biomecánico del contacto con el balón en el saque del voleibol de playa - Diaz Agramonte, A.; Canizares Zolano, R. G.; Leon Pérez, S.; Rodriguez Leal, E. A. (Revista Cubana de medicina del deporte y la cultura fisica, 2016)
The present article contains the results of the elaboration of a biomechanical model of the contact phase with the ball in the serve in suspension with effect in the beach volleyball. The biomechanical study give the fundamental indicators present in the execution of the action in two athletes of the team beach volleyball 14-15 years of the county Ciego de Ávila through the observation of the video recorder carried out to the effect, to describe the fundamental technical elements from the biokinematic point of view and the characteristics that determine these in an upward way and they define the correct realization of the motive task.